Electret prevents the formation of bacterial biofilm - Zhipeng Sun; Hongbao Wang; Xin Guo; Jiajie Xu; Hejuan Liang; Jian Jiang; Yuanyuan Liang (IET Nanodielectrics, 2023)
Abstract Bacterial biofilm formation is an important factor in bacterial resistance. The commonly used methods to inhibit bacterial biofilms are synthetic drugs such as antimicrobial peptides, but physical methods are often safe, non‐toxic and simple to prepare. This work proposes an environmentally friendly method to use electret films to provide a stable electric field during the formation of bacterial biofilms, inhibit the formation of bacterial biofilms through the action of the electric field and weaken the adhesion of bacterial biofilms. The total amount of Staphylococcus aureus biofilm decreased by 20% compared to the control group after the treatment of positive electret. The distribution of exopolysaccharides showed that the activity of biofilm also decreased. In addition, the negative electret can also inhibit the formation of bacterial biofilm. The result can be generalised to other Gram‐positive bacteria and could contribute to reduce the resistance of bacteria, improve the effect of related antibiotics, reduce the dosage of antibiotics and reduce the side effects of drugs.